Legacy effect of green manure crops fertilized with calcium phosphite on maize production and soil properties. (1st October 2021) - Fontana, Mario; Guillaume, Thomas; Bragazza, Luca; Elfouki, Saïd; Santonja, Mathieu; Buttler, Alexandre; Gerdol, Renato; Brancaleoni, Lisa; Sinaj, Sokrat
Abstract: Recycling phosphorus (P) is crucial to meet future P demand for crop production. We investigated the possibility to use calcium phosphite ( Ca-Phi ) waste, an industrial by-product, as P fertilizer following the oxidation of phosphite (Phi) to phosphate (Pi) during green manure (GM) cropping in order to target P nutrition of subsequent maize crop. In a greenhouse experiment, four GM crops were fertilized (38 kg P ha −1 ) with Ca-Phi, triple super phosphate ( TSP ) or without P ( Control ) in sandy and clay soils. The harvested GM biomass (containing Phi after Ca-Phi fertilization) was incorporated into the soil before maize sowing. Incorporation of GM residues containing Phi slowed down organic carbon mineralization in clay soil and mass loss of GM residues in sandy soil. Microbial enzymatic activities were affected by Ca-Phi and TSP fertilization at the end of maize crop whereas microbial biomass was similarly influenced by TSP and Ca-Phi in both soils. Compared to Control, Ca-Phi and TSP increased similarly the available P (up to 5 mg P kg −1 ) in sandy soil, whereas in clay soil available P increased only with Ca-Phi (up to 6 mg P kg −1 ), indicating that Phi oxidation occurred during GM crops. Accordingly, no Phi was found in maize biomass. However, P fertilization did not enhance aboveground maize productivity and P export, likely because soil available P was not limiting. Overall, our results indicate that Ca-Phi might be used as P source for a subsequent crop since Phi undergoes oxidation during the preliminary GM growth. Highlights: Plant residues containing phosphite affected microbial properties in clay soil. Decomposing rate of plant residues containing phosphite decreased in sandy soil. Green manure oxidized phosphite to provided phosphate for a following maize crop. Maize did not contain phosphite after green manure fertilized with calcium phosphite. Calcium phosphite increased available P similarly as triple super phosphate.